Pengaruh Diversifikasi Produk, Daya Tarik Wisata dan Harga Tiket terhadap Minat Kunjung Ulang Wisatawan - Dinda Azolla Yundi Afi; Novita Putri Diantanti; Anwar Hakim Darajat (Tamasya : Jurnal Pariwisata Indonesia, 2024)
This study aims to determine the effect of product diversification, tourist attraction and ticket prices on tourist re-visit interest in Kampung Coklat Blitar educational tourism (quantitative study on Balitar Islamic University students). The research method used was a survey with a quantitative research approach. The sampling technique used was purposive sampling. Data collection was carried out by distributing questionnaires to Balitar Islamic University students as respondents who had visited the Kampung Coklat educational tour. The data analysis techniques used are partial test (t), simultaneous test (f) and multiple linear analysis. Based on the results of the partial test conducted, it is known that the variables of product diversification and tourist attraction have a significant effect on the variable of re-visit interest, while the ticket price variable does not have a significant effect on the variable of re-visit interest. Then, based on the results of the simultaneous test conducted, it is known that the variables of product diversification, tourist attraction and ticket prices simultaneously or together have a significant effect on re-visit interest.